Economic Debate On Financing Model of The National Health System - Anwar, Syaiful; Bachtiar, Nasri; Fahmy, Rahmy (Devotion : Journal of Research and Community Service, 2023)
The topic of health-care financing is becoming increasingly important, particularly in light of the Covid-19 pandemic. In this study, we examine the pattern of funding for the national health system from the standpoint of economic thought, as well as the role of government in the context of macroeconomic analysis of social welfare. Conceptual Analysis is the method employed. The data used is based on related theory. This study discovered that health issues are social welfare issues as one of the macroeconomic goals. The macroeconomic debate employs an interdisciplinary framework in which the determinants include external shocks and policy levers, while the pure or theoretical ones are descriptive and applied, resulting in outputs such as prices, growth, output, and international balances. In theory, government involvement in the economy can be divided into two extremes: the classical view and the Keynesian view. The problem of wage and price flexibility, self-adjustment, and government intervention is the result of these two views, though there is a middle view; Schumpeter. The health system can be funded in three ways: entirely by the government, partially by the government, and entirely by the private sector or the public. Furthermore, the cost of health insurance is influenced by the economy, competition, rules, company goals, market structure, government intervention, and a variety of other factors. In the future, studies must be conducted using big data